Analisis Penerapan SAK-EMKM Pada UMKM Kuliner di Kota Pontianak - Alfatih, Ridho; Kurniawan, Rudy; Mustika, Ira Grania (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
MSMEs are vital to Indonesia’s economy, including in Pontianak City, yet many, especially in the culinary sector, struggle with non-standardized financial management. This study analyzes the implementation of SAK-EMKM among culinary MSMEs in Pontianak using qualitative, phenomenological methods through in-depth interviews. Findings show most MSMEs have not adopted SAK-EMKM due to limited understanding, resources, and the belief that simple records suffice. Other barriers include lack of socialization, time, and cost. Despite this, MSME actors recognize the importance of structured financial reporting and show interest in technology-based solutions. The study recommends practical training, user-friendly accounting apps, and university collaboration to enhance SAK-EMKM adoption.